Involvement of Inner Choroidal Layer in Choroidal Thinning during Regression of Multiple Evanescent White Dot Syndrome - Yuki Hashimoto; Wataru Saito; Yuka Hasegawa; Kousuke Noda; Susumu Ishida (Journal of Ophthalmology)
Purpose. To investigate relationships between total thickness and the thickness of inner and outer layers in the choroid during regression in patients with multiple evanescent white dot syndrome (MEWDS). Methods. This retrospective observational case series included 15 unilaterally affected eyes and 13 unaffected fellow eyes from 15 MEWDS patients (4 men and 11 women; mean age, 37.6 ± 17.6 years). Using enhanced depth imaging optical coherence tomography, whole, inner, and outer choroidal layer thicknesses at the fovea and perifovea were manually measured at the initial visit and at 1 and 3 months after the initial visit. The mean thickness values of the layers were compared at each stage. Results. With regression of MEWDS, the mean subfoveal whole and inner choroidal layer thicknesses significantly decreased at 1 and 3 months compared to baseline values in MEWDS eyes (P=0.01 and P<0.0001, respectively), but not in fellow eyes. The outer layer in MEWDS eyes tended to thin. Changes in the inner and outer layers at the perifovea in MEWDS eyes also showed the same trends. Simple linear regression analysis revealed significant positive correlations in choroidal thickness changes between the whole and inner layers (R = 0.53, P=0.04) and between the whole and outer layers (R = 0.91, P<0.0001) from baseline to 3 months. Multiple linear regression analysis revealed that choroidal thickness changes in the whole layer were significantly correlated with those in the inner (β = 0.51, P<0.0001) and outer (β = 0.73, P<0.0001) layers. Conclusion. The inner choroidal layer significantly thinned with regression of MEWDS, correlating with the thinning of total choroidal thickness. These results suggest that MEWDS lesions in the choroid are likely to lie mainly in the inner layer.